COVID-19 and the immobility turn - Cairns, D.; Clemente, M. (The immobility turn: Mobility, migration and the covid-19 pandemic, 2023)
The Immobility Turn is about transformations that have taken place in geographical mobility since the start of the COVID-19 pandemic, with long periods of restricted access to international and interregional circulation constituting a loss of the previously taken-for-granted freedom to travel. This extends to creating difficulties for industries that had grown reliant on free circulation of people – most prominently, tourism, universities and businesses employing large numbers of migrant labourers. Such is the scale of these transformations that there may have been a change in the pivotal position occupied by mobility in many societies, leading us to hypothesize that an ‘immobility turn’ has taken place. This follows on from the preceding ‘mobility turn’, which can be seen as a way of theorizing the multiplication of mobility in social, economic and political life, taking advantage of expanded levels of global interconnectedness.